2014
DOI: 10.1111/1348-0421.12147
|View full text |Cite
|
Sign up to set email alerts
|

V‐antigen homologs in pathogenic gram‐negative bacteria

Abstract: Gram-negative bacteria cause many types of infections in animals from fish and shrimps to humans. Bacteria use Type III secretion systems (TTSSs) to translocate their toxins directly into eukaryotic cells. The V-antigen is a multifunctional protein required for the TTSS in Yersinia and Pseudomonas aeruginosa. V-antigen vaccines and anti-V-antigen antisera confer protection against Yersinia or P. aeruginosa infections in animal models. The V-antigen forms a pentameric cap structure at the tip of the Type III se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 132 publications
0
28
0
Order By: Relevance
“…Our target is PcrV, which forms the tip of the type III secretion apparatus responsible for the delivery of type III secretory toxins (i.e., ExoS, ExoT, ExoU, and ExoY) into target cells. 12 Based on the preclinical data for the mAb166 murine anti-PcrV monoclonal antibody in various animal models, 19,20,22,39 a humaneered anti-PcrV monoclonal antibody (KB001-A, KaloBios Pharmaceuticals) has been developed 23 and tested for treating P. aeruginosa pneumonia in patients with cystic fibrosis and in mechanically ventilated patients in Phase II studies in the United States 24 and France. 25 Although Figure 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our target is PcrV, which forms the tip of the type III secretion apparatus responsible for the delivery of type III secretory toxins (i.e., ExoS, ExoT, ExoU, and ExoY) into target cells. 12 Based on the preclinical data for the mAb166 murine anti-PcrV monoclonal antibody in various animal models, 19,20,22,39 a humaneered anti-PcrV monoclonal antibody (KB001-A, KaloBios Pharmaceuticals) has been developed 23 and tested for treating P. aeruginosa pneumonia in patients with cystic fibrosis and in mechanically ventilated patients in Phase II studies in the United States 24 and France. 25 Although Figure 10.…”
Section: Discussionmentioning
confidence: 99%
“…11 In the type III secretion system of P. aeruginosa, PcrV, a cap structure on the tip of the type III secretory apparatus, is a key molecule through which cytotoxic P. aeruginosa delivers lethal cytotoxic toxins into its target eukaryotic cells. 12 We have previously reported that the blockade of PcrV by specific antibodies can inhibit translocation of type III secretory toxins. 10,13,14 Active immunization with recombinant PcrV protects animals from lethal P. aeruginosa infections [14][15][16] , and anti-PcrV antibodies also protect infected animals from acute lung injury, bacteremia, and sepsis.…”
Section: Introductionmentioning
confidence: 98%
“…Conservation of the TTSS has been discussed and demonstrated in other studies [34][35][36][37]. Assessment of the health records of the study subjects did not uncover any unreported health conditions and no veterinary adverse health observations were made.…”
Section: Functionality Of Omv-elicited Igg Antibodiesmentioning
confidence: 83%
“…208 Subsequently, this plasmid-encoded secreted protein was also identified in all human pathogenic Yersinia (for recent review see ref. 209 ). Interestingly, homologs of LcrV are also expressed by several other bacteria employing a T3SS such as P. aeruginosa, V. cholerae, Photorhabdus luminescens and Aeromonas spp.…”
Section: Structure and Functionmentioning
confidence: 99%
“…Interestingly, homologs of LcrV are also expressed by several other bacteria employing a T3SS such as P. aeruginosa, V. cholerae, Photorhabdus luminescens and Aeromonas spp. 209 However, quite surprisingly neither any possible intracellular target(s) nor an enzymatic activity has been associated with LcrV yet. Furthermore, LcrV has been intensely studied as part of candidate vaccines against Yersinia infections and has been shown to confer protection in animal models.…”
Section: Structure and Functionmentioning
confidence: 99%